Sosialisasi Ilmu Pengetahuan tentang Peran Orang Tua dalam Pendampingan Pembelajaran Daring - Nurmalina Nurmalina; Yunie Amalia Rakhmyta (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2022)
Online learning is one of the government's policies in an effort to prevent the spread of the COVID-19 virus. The role of parents in online learning includes: 1) Accompanying students in every online learning process, 2) Facilitating students in carrying out various learning activities; 3) Motivating students so that they feel happy, happy, and complete learning activities well. Strategies in educating children at home include: 1. Make a schedule of activities that are carried out regularly at home; 2. Use online facilities at home; 3. Be flexible when the child is bored at home; 4. Creative and innovative looking for activities together with family members; 5. Invite children to exercise; 6. Explain that this covid-19 period is only temporary; 7. Make children happy in doing activities. Obstacles faced by parents in online learning are: 1. Parents' understanding of the child's subject matter is lacking; 2. Time to accompany the child; 3. Inaccessibility of the internet network in the area of residence; 4. Limited internet quota; 5. Lack of understanding of the use of technology.